(untitled) (The Planet, 2021)
Tuberculosis (TB) is still one of the deadly infectious diseases worldwide. It is estimated that around one-third of the world’s population is infected with latent TB (LTBI) with 5–10% life time risk of developing active TB [1, 2]. Presence of good diagnosis is important for the control and ultimate elimination of the disease [3]. However, diagnosis of LTBI and active TB using the existing tools is challenged by low sensitivity (in smear microscopy); need of prolonged time for results and need of sophisticated laboratories and expertise (in TB culture) [4]; relatively expensive and heterogeneous diagnostic accuracy (in molecular techniques) [5]; false positive reactions [6], lower sensitivity in immune-suppressed peoples [6, 7], anamnestic recall of immunity [8], potential for inter- and intra- operator variability of results [9], inconvenience for patients in tuberculin skin test, a test, based on the fact that infection with M. tuberculosis bacterium produces a delayed-type hypersensitivity skin reaction to certain components of the bacterium [10]. Putting all the challenges of the techniques together reinforces the need for improved diagnostic tools Recently, important advances have been achieved in these fields that have led to substantial improvements in the accuracy and the timing of the diagnosis of tuberculosis. Novel methods allow for a better identification of latently infected individuals who are at risk of developing active tuberculosis, they also offer the possibility for a rapid diagnosis of active tuberculosis in patients with negative sputum smears for acid-fast bacilli and enable prompt identification of drug-resistant strains of Mycobacterium tuberculosis directly from respiratory specimen with a high accuracy. In addition, promising methods that will further optimize the diagnosis of tuberculosis are under development. In the future, therapeutic interventions based on the results of novel diagnostic procedures can be made earlier leading to improvements in patient care.